Republic of Moldova : Poverty Reduction Strategy Paper; National Development Strategy Report for 2008-2011. (IMF Staff Country Reports; Country Report ;, 2008)
The purpose of the monitoring and evaluation process is to determine to what extent proposed actions/sub-actions have been accomplished, and to take policy corrective action to accomplish the objectives of the National Development Strategy. Monitoring and evaluation is done on the basis of process and performance indicators. The monitoring process will generate progress reports and will be reported at sixth-month intervals. A report on the evaluation of the National Development Strategy will be prepared at the end of each year of implementation.